Pseudoclypeina? crnogorica Radoičić, 1972: Stratigraphic revision and taxonomic note on a little known dasycladalean alga from Montenegro - Radoičić Rajka; Carras Nicolaos; Conrad Marc Andre (Geološki Anali Balkanskoga Poluostrva, 2013)
Pseudoclypeina? crnogorica was first described in 1972 from the Lower, Cretaceous limestone of the Njegoš Mt. area, Montenegro, Dinaric Carbonate Platform. It differs from other species of the genus Pseudoclypeina by its calcification pattern, the shape and relative length of the first and second order laterals, and by the presence in the type-material (a thin section containing the holotype) of sections standing for the sterile portion of the thallus. This is why in this paper, the generic name is left in open nomenclature. On this occasion the species, whose presence is also reported from southern Iran, is re-described and better illustrated, based on material originating from other outcrops in Montenegro. The stratigraphic position is reviewed as well. Pseudoclypeina? crnogorica occurs in shallow water inner platform facies of early Neocomian age, along with Selliporella neocomiensis.